2012
DOI: 10.4236/jmmce.2012.118071
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth, Optical and Dielectric Properties of L-Histidine Hydrochloride Monohydrate Nonlinear Optical Single Crystals

Abstract: Optically transparent and bulk single crystal of l-histidine hydrochloride monohydrate (LHHM) was successfully grown by slow evaporation technique. The cell parameters and the crystallinity of the grown crystal were estimated by the single crystal XRD. Optical transmittance of the crystal was recorded using the UV-vis-NIR spectrophotometer. The optical band gap and optical constant of the material were determined by using transmission spectrum. The dielectric loss and dielectric constant measurements as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a direct band gap material 14 , the crystal under study has an absorption coefficient (α) obeying the following relation for high photon energies (hν) [10] Figure 2. Powder X-ray diffraction pattern for GZS crystal.…”
Section: Uv-vis-nir Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a direct band gap material 14 , the crystal under study has an absorption coefficient (α) obeying the following relation for high photon energies (hν) [10] Figure 2. Powder X-ray diffraction pattern for GZS crystal.…”
Section: Uv-vis-nir Spectral Analysismentioning
confidence: 99%
“…A plot of variation of (αhν) 2 versus hν is shown in Figure 4. E g is evaluated using the extrapolation of the linear part 14 . Using Tauc's plot, the energy gap (E g ) was calculated as 5.40 eV and the large band gap clearly indicates the wide transparency of the crystal.…”
Section: Figure 3 Uv-vis Transmission Spectrum Of Gzs Materials Resmentioning
confidence: 99%
“…E g was evaluated using the extrapolation of the linear part [23]. Using the Tauc plot, the energy gap (E g ) was calculated to be 4.80 eV and the large band gap clearly indicated the wide transparency of the crystal [24]. This high band gap value indicated that the grown crystal possessed dielectric behaviour to induce polarization when powerful radiation was incident on the material.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%